Meta-analysis on the chronic effects of exercise on depression in older adults - Melanie Mack; Claudia Voelcker-Rehage; Pinelopi S. Stavrinou; Iuliia Pavlova; Yaël Netz; Burcu Kömürcü Akik; Antonia Kaltsatou; Sandra Haider; Christoforos D. Giannaki; Arzu Erden; Andreea Badache; Michel Audiffren (Current Issues in Sport Science)
Introduction This review aimed to investigate the effects of chronic exercise on depression severity and various depressive symptoms in Randomized Controlled Trials (RCTs) including older adults with an average age of at least 60 years and a minimum level of mild depression. Thereby, the moderating effects of various intervention and individual characteristics were considered.